Analysis of The Projectile Motion was Blocked in Gun Bore. Issue 1 (January 2021) - Guo, Zhaowei
Abstract: To learn the security of projectile was blocked when high-speed movement in gun bore, interior pressure and the movement of projectile were calculated and analyzed under different postulated conditions. Through the analysis of the change in interior pressure after the projectile, the character of projectile was restricted in gun bore during movement and the pressure on both barrel and projectile, also by these to check security in the design of barrel and projectile, and identified the matching problems which needed careful attention in the design processes of both gun and ammunition.